Modelling Steady State and Transient Stability Parameters for Kainji Hydropower Station, Nigeria - Adu, Michael Rotimi; Melodi, Adegoke Oladipo; Onimisi, John O. (Advanced engineering forum, 2024)
The study explores the creation of a simulator for addressing the problem of predicting response of Nigeria’s Kainji’s Hydro Power Plant (KHPP) to system load variations and to determine parameters for stable operation. A virtual KHPP Simulation Model was designed and created using MatLab/Simulink software. The components of the HSS designed and incorporated in the virtual simulator include models of all eight (8) generating units (GUs). Each GU model consists of the Hydraulic Turbine Governor (PID), synchronous generator and an excitation system. The simulator was tested with steady state stability (SSS) and transient stability (TS) disturbances to obtain response values of system operating state parameters. The tests include a variable load increase, and three-phase short circuit fault for a duration of 0.2 s. The SSS limits established are the following: active load – 810 MW, load angle – 850, terminal voltage 0.68 pu, rotor speed 1.08 pu, excitation voltage 1.55 pu, and stator current 7.5 pu. TS limits established are load angle (1700), terminal voltage (0.60 pu), rotor speed (1.05) pu, excitation voltage (1.25 pu), stator current (7.1 pu), and critical clearing time (0.2s). Clearing time should be set at 0.2s to prevent KHPP and connected system’s instability.